2019
DOI: 10.29133/yyutbd.426847
|View full text |Cite
|
Sign up to set email alerts
|

Change in Soil Temperature Depending on Surface Heat Flow

Abstract: Öz: Sıcaklık dalgalarının toprak yüzeyinde ve alt katmanlarında dağılımı, toprak özelliklerinin yanı sıra, toprakların ısı kapasitesi, ısısal yayınım, ısı iletkenliği ve yüzey ısı akışı gibi ısısal özelliklerine de önemli düzeyde bağlıdır. Bu çalışmada, (i) toprak yüzeyinde ısı akışının sabit olması durumunda ısı akışı denkleminin çözümüne ve Fourier kuralına göre toprak yüzey sıcaklığının değişimi irdelenmiş, (ii) toprağın yüzey ısı akışı, yüzey ve alt katman sıcaklıklarının, ısısal yayınımın ve zamanın bir f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…It is observed that while the researches related to yield and facilitating selection studies were carried out intensely un-til 1999, they decreased from 2000 and onward. It is known that earliness in maturity has increased and maturity periods are reduced due to the effects of phenological deviations resulting from global climate change, which has accelerated recently (Penuelas and Filella 2001;Walther et al, 2002;Craufurd and Wheeler, 2009;Visser et al, 2010;Sayılğan, 2016;Yavaş and Ünay, 2018;Gülser et al, 2019). In order to develop varieties with high adaptation to these conditions, revealing the effects of phenological features and new developments in plant morphology on yield is important in terms of the success of the breeding programs and prospective predictability.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that while the researches related to yield and facilitating selection studies were carried out intensely un-til 1999, they decreased from 2000 and onward. It is known that earliness in maturity has increased and maturity periods are reduced due to the effects of phenological deviations resulting from global climate change, which has accelerated recently (Penuelas and Filella 2001;Walther et al, 2002;Craufurd and Wheeler, 2009;Visser et al, 2010;Sayılğan, 2016;Yavaş and Ünay, 2018;Gülser et al, 2019). In order to develop varieties with high adaptation to these conditions, revealing the effects of phenological features and new developments in plant morphology on yield is important in terms of the success of the breeding programs and prospective predictability.…”
Section: Discussionmentioning
confidence: 99%
“…The implications of increasing volumetric heat capacity in the soils under different land use types showed there is a positive correlation between volumetric water content and volumetric heat capacity. Gülser et al (2019) showed that volumetric heat capacity increased from 0.497 cal cm -3 °C to 0.541 cal cm -3 °C by increasing volumetric water content from 0.286 cm 3 cm -3 to 0.330 cm 3 cm -3 . The higher volumetric heat capacity of the soil under continuously cultivated soil and forest land is probably due to adsorption of water (from soil moisture content) forming thick hulls around the soil particles, which greatly enhanced its effective heat capacity (Abu-Hamdeh, 2003).…”
Section: Thermal Conductivitymentioning
confidence: 98%